Pulsed Field Ablation for Hepatocellular Carcinoma: From Technological Evolution to Clinical Translation - Min Xu; Yuhang Wang; Danxia Xu; Jinhua Pan; Chengyue Zhang; Mengmeng Li; Qiyu Zhao; Tian’an Jiang (Bioelectromagnetics in Medicine, 2026)
Pulsed electric field (PEF) ablation is an emerging non-thermal ablation approach for hepatocellular carcinoma (HCC), with unique bioelectrical effects and potential advantages in treating tumors adjacent to critical structures. This review summarizes recent advances in PEF technologies, including irreversible electroporation (IRE), nanosecond pulsed electric field (nsPEF), and high-frequency irreversible electroporation (H-FIRE), focusing on biological mechanisms, clinical evidence, and future perspectives. Current studies suggest that PEF ablation achieves promising local tumor control and favorable safety profiles in selected HCC patients, particularly those with perivascular and perihilar tumors unsuitable for thermal ablation. However, current evidence remains limited by retrospective study designs, heterogeneous pulse protocols, and the absence of prospective randomized trials. Emerging data indicate that PEF may reshape the tumor immune microenvironment, supporting its potential combination with immune checkpoint inhibitors and other immunotherapies. Future research should prioritize prospective validation, protocol standardization, and mechanistic studies to further define the role of PEF in multidisciplinary HCC management.